2009
DOI: 10.1007/s00167-009-0871-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of arthroscopic all-inside meniscus repairs

Abstract: Viper is a new device for arthroscopically all-inside meniscal repairing. In previous studies about Viper device, procedures were not applied arthroscopically despite this device has been designed for arthroscopic application. In this study, we evaluated primary fixation strength of arthroscopically applied meniscal repair using Viper device to obtain better clinical relevance. Two centimeter in length meniscal tear 2-3 mm far from periferic edge of medial meniscus of 50 calves were created arthroscopically. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
0
20
1
1
Order By: Relevance
“…72 The all inside technique has shown that fixation with the most recent repair devices is as strong and as reliable as outside-in technique. 73 Currently, all three techniques are considered effective options for tear fixation and can be used with equal clinical effectiveness.…”
Section: Treatmentmentioning
confidence: 99%
“…72 The all inside technique has shown that fixation with the most recent repair devices is as strong and as reliable as outside-in technique. 73 Currently, all three techniques are considered effective options for tear fixation and can be used with equal clinical effectiveness.…”
Section: Treatmentmentioning
confidence: 99%
“…These devices can create repairs similar in strength to outside-in techniques and stronger than other allinside techniques. 55,57 The inside-out technique remains the gold standard for meniscal repair, 58 especially for large tears and buckethandle tears that require a significant number of sutures. A systematic review, comparing inside-out to all-inside repairs, demonstrated no differences in healing rates, functional outcomes, and complication rates.…”
Section: Operative Goals and Optionsmentioning
confidence: 99%
“…Fourth generation repair devices allow the placement of sutures in the meniscus without using an incision or a fixator system 17 . Gunes et al 33 , in their mechanical study, concluded that these repair devices outcome studies have demonstrated that repairs of the meniscus performed concurrently with ACL reconstruction are more successful than repairs done in ACL-intact knees. Therefore, it is generally recommended that ACL reconstruction and meniscal repair should be done concurrently 29,30 .…”
Section: All-inside Techniquementioning
confidence: 99%